Payout policy in the 21st century - Brav, Alon; Graham, John R.; Harvey, Campbell R.; Michaely, Roni (Journal of Financial Economics, 2005)
We survey 384 financial executives and conduct in-depth interviews with an additional 23 to determine the factors that drive dividend and share repurchase decisions. Our findings indicate that maintaining the dividend level is on par with investment decisions, while repurchases are made out of the residual cash flow after investment spending. Perceived stability of future earnings still affects dividend policy as in Lintner (1956. American Economic Review 46, 97–113). However, 50 years later, we find that the link between dividends and earnings has weakened. Many managers now favor repurchases because they are viewed as being more flexible than dividends and can be used in an attempt to time the equity market or to increase earnings per share. Executives believe that institutions are indifferent between dividends and repurchases and that payout policies have little impact on their investor clientele. In general, management views provide little support for agency, signaling, and clientele hypotheses of payout policy. Tax considerations play a secondary role.